Protecting Free Trade : the Hong Kong Paradox 1947-97. - Mills, Lawrence (Hong Kong University Press, HKU, 2012)
Protecting Free Trade traces the story of a paradox that both limited and stimulated Hong Kong's post-war economy. In order to preserve its comƯmitment to open markets, Hong Kong was obligated by international agreements to accept restraints on its exƯports; and in order to sustain its growth and development, Hong Kong had to subject its largest industry--textiles--to a massive network of restricƯtions. The focus is on how Hong Kong handled, through negotiation, attempts by develƯoped economies to limit interƯnational trade through protecƯtive measures.